Application of Lithium Assay kit LS for quantification of lithium in whole blood and urine. (March 2021) - Iwai, Masae; Kondo, Fumio; Suzuki, Takayoshi; Ogawa, Tadashi; Seno, Hiroshi
Highlights: Lithium is widely used in the treatment of bipolar disorders. Quantification of lithium in blood and urine is important. This paper described an application of the Lithium Assay kit LS for quantification of lithium. The Lithium Assay kit LS appears to be useful for forensic toxicological investigations. Abstract: A commercially available kit for the quantitation of lithium, the Lithium Assay kit LS, was originally developed to measure lithium in serum or plasma using a conventional microplate reader. We investigated whether use of the kit could be extended to quantify lithium in whole blood and urine samples collected at autopsy. The calibration curve for whole blood showed good linearity ranging from 0.5 to 20 µg/mL with a coefficient of determination of 0.998 when samples were pretreated with methanol followed by acetonitrile. Moreover, for urine, we obtained excellent linearity with a coefficient of determination of 0.999 without any pretreatment. The accuracies and precisions were 106.3–174.7% and 1.9–18.1% for whole blood and 83.3–118.8% and 5.7–33.8% for urine. The values in the lower concentration range (0.5–1 µg/mL) were not satisfactory, whereas those in the higher range (2–20 µg/mL) were acceptable. The Lithium Assay kit LS was successfully applied to the measurement of lithium in whole blood and urine samples collected at autopsies. This method appears to be useful for forensic toxicological investigations because of its simplicity and speed.